34th European Congress of Pathology - Abstracts. (Virchows Archiv: European Journal of Pathology)
The intensity of FOXA1 expression was higher in the group without lymph node BC metastasis 94 cases(41.6%) compared to the group with lymph node BC metastasis 37 cases(28.2%). B Results: b FOXA1-expression significantly correlates with clinicopathological and immunohistochemical parameters, including those that have a predictive value in the process of lymph node BC metastasis, such as the patient's age(p=0.004), tumour node size(p=0.028), Grade(p=0.001), ER(p<0.001) and PgR-expression(p=0.003), Ki-67(p<0.001). B PS-01-022 b B Pathological features of CT-guided bone lesion biopsy specimens in breast cancer patients b U M. Abramovic* u , L. Korsa, L. Grbanovi'c, M. Cavka, I. Svagelj, M. Prutki, Z. Marusi'c *Clinical Department of Pathology and Cytology, University Hospital Centre Zagreb, Croatia B Background & objectives: b Current breast cancer guidelines recommend biopsy of metastatic lesions at presentation or first recurrence. B PS-01-026 b B Predictive factors of lymph node metastasis in breast cancer patients: a Croatian population-based study b U Z. Radicevi'c* u , J. Rajc, D. Damjanovi'c, R. Gudelj, M. Bakula, R. Alaghehbandan *University Hospital Osijek, Croatia B Background & objectives: b Breast cancers are heterogeneous groups of tumours, and its subtypes correlates with therapeutic response and overall survival.